2022
DOI: 10.1002/iub.2659
|View full text |Cite
|
Sign up to set email alerts
|

Decreased differentiation capacity and altered expression of extracellular matrix components in irradiation‐mediated senescent human breast adipose‐derived stem cells

Abstract: Radiotherapy is widely used for the treatment of breast cancer. However, we have shown that ionizing radiation can provoke premature senescence in breast stromal cells. In particular, breast stromal fibroblasts can become senescent after irradiation both in vitro and in vivo and they express an inflammatory phenotype and an altered profile of extracellular matrix components, thus facilitating tumor progression. Adipose-derived stem cells (ASCs) represent another major component of the breast tissue stroma. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…Moreover, numerous investigations have demonstrated that CD44 is a cell surface marker of preadipocytes and mesenchymal stem cells. We speculate that CD44 also plays an equally important role in the differentiation of mesenchymal stem cells into preadipocytes during the entire process of cell differentiation. In light of the abovementioned findings, it is still quite exciting to speculate about the hidden molecular processes by which CD44 controls lipid metabolism.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, numerous investigations have demonstrated that CD44 is a cell surface marker of preadipocytes and mesenchymal stem cells. We speculate that CD44 also plays an equally important role in the differentiation of mesenchymal stem cells into preadipocytes during the entire process of cell differentiation. In light of the abovementioned findings, it is still quite exciting to speculate about the hidden molecular processes by which CD44 controls lipid metabolism.…”
Section: Discussionmentioning
confidence: 89%
“…For instance, the overexpression of CD44 was reported to reduce the levels of MMPs for the maintenance of ECM homeostasis 174 . In Papadopoulou's study, 175 the increase in MMP1 and MMP13 expression followed by the decreased expression levels of CD44 was found to promote tumor growth. Another study also showed that MMP2 activation contributed to decrease the number of CD44 + /CD24 − cells in MDA‐MB‐231 cells after normothermic microwave treatment 176 .…”
Section: Cd44 In Neoplastic Diseasesmentioning
confidence: 99%
“…Novel DNA synthesis was performed with dual labeling with 5-bromo-2 ′ -deoxyuridine (BrdU) and 4 ′ ,6-diamino-2-phenylindole (DAPI) dihydrochloride (Sigma, Kawasaki City, Japan) [1][2][3]. Furthermore, ADSCs' cell surface markers were examined, as described before [27].…”
Section: Isolation and Culture Of Adscsmentioning
confidence: 99%